2013
DOI: 10.1063/1.4817189
|View full text |Cite
|
Sign up to set email alerts
|

Are trinuclear superhalogens promising candidates for building blocks of novel magnetic materials? A theoretical prospect from combined broken-symmetry density functional theory and ab initio study

Abstract: The structures, relative stabilities, vertical electron detachment energies, and magnetic properties of a series of trinuclear clusters are explored via combined broken-symmetry density functional theory and ab initio study. Several exchange-correlation functionals are utilized to investigate the effects of different halogen elements and central atoms on the properties of the clusters. These clusters are shown to possess stronger superhalogen properties than previously reported dinuclear superhalogens. The cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 91 publications
(128 reference statements)
1
18
0
Order By: Relevance
“…Polynuclear superhalogens (M n X n · k + 1 ), of which the number of central atoms ( n ) is larger than one, take advantage of increasing the number of ligands while maintaining their high stability and, therefore, exploring polynuclear superhalogens has become an essential novel research direction (see Refs. and references cited therein). Examples include magnesia halogens whose electron affinities do not only confirm their superhalogen nature but also reveal a strong relationship with the number of central metal atoms.…”
Section: Introductionmentioning
confidence: 99%
“…Polynuclear superhalogens (M n X n · k + 1 ), of which the number of central atoms ( n ) is larger than one, take advantage of increasing the number of ligands while maintaining their high stability and, therefore, exploring polynuclear superhalogens has become an essential novel research direction (see Refs. and references cited therein). Examples include magnesia halogens whose electron affinities do not only confirm their superhalogen nature but also reveal a strong relationship with the number of central metal atoms.…”
Section: Introductionmentioning
confidence: 99%
“…The utility of superhalogens in the design and synthesis of new materials of technological importance has spurred considerable interest not only in expanding their scope but also in finding ways to enhance their electron affinities. Recent works have shown that superhalogens are not restricted to just a metal atom at the core surrounded by halogen atoms but can be created when the core atom is replaced by a cluster, when the ligands are no longer halogen atoms, and even when none of the constituents are metal or halogen atoms . Equally important, a new class of electronegative clusters called hyperhalogens has emerged where the halogen ligands are replaced by superhalogen ligands, enabling their electron affinities to surpass those of their superhalogen building blocks.…”
Section: Introductionmentioning
confidence: 99%
“…H. Yang et al designed hetero‐binuclear superhalogen anions with cyanides and isocyanides as ligands . We have also found that there are several superhalogens are available in the literature such as binuclear, trinuclear and polynuclear superhalogens, iron‐based magnetic superhalogens, antiferromagnetic binary hyperhalogen, novel superhalogens with metal oxyfluoride ligands, traditional halogen based superhalogens and N5‐based aromatic hyperhalogen anions . The application of superhalogens are also manifold.…”
Section: Introductionmentioning
confidence: 80%